Reviews of new publications - Holmes, Derek A (KUKILA, 1992)
ICBP (1992). Putting diversity on the map: priority areas for global conservation. Cambridge, U.K.: International Council for Bird Preservation. Dickinson, E.G., Kennedy, R.S. & K.C. Parkes. 1991. The birds of The Philippines, an annotated check-list. BOU Check-list No. 12. British Ornithologist’s Union, Tring. Hong Kong Bird Report 1991. Published by the Hong Kong Bird Watching Society. Papua New Guinea Bird Calls. H & A Crouch. Two cassettes published by the Papua New Guinea Bird Society, Box 1598, Boroko, PNG.